Amplification refractory mutation system-PCR is essential for the detection of chimaeras with a minor allele population: a case report. Issue 5 (15th February 2013) - Won, Eun Jeong; Park, Hye Ryoen; Park, Tae Sung; Oh, Seung Hwan; Shin, Myung Geun; Shin, Jong Hee; Suh, Soon Pal; Ryang, Dong Wook; Park, Jong Tae; Cho, Duck
Abstract : Blood chimaera is a rare but important issue for immunohaematology laboratories. Several molecular approaches, such as ABO genotyping, human leucocyte antigen (HLA) typing and DNA short tandem repeat (STR) analysis, have been used to identify chimaerism. Unfortunately, the minor allele population can be overlooked by PCR-based methods, which preferentially amplify the major allele population. A case with Aweak B (Aw B), demonstrating a mixed-field pattern, was sent to our laboratory for further evaluation. Direct sequencing of ABO exons 6 and 7 revealed a B101/O02 genotype. Analysis of the 12 STR loci and HLA typing did not provide any evidence of chimaerism. However, amplification refractory mutation system (ARMS)-PCR identified the minor A102 allele in addition to B101/O02. Three alleles of the chimaera were confirmed by cloning and sequencing. Thus, ARMS-PCR is essential, especially in the case of a chimaera with a minor allele population.